Transforming Diversity into Character: A Contextual Study of Multicultural Education Practices in Grade IX at SMP Negeri 1 Kotapinang, Indonesia - Dalimunthe, Aldi Wijaya; Br. Rambe, Siti Aisyah; M. Hafiz, M. Hafiz; Erdianto, Rudy; Albina, Meyniar (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Multicultural education has a vital role in instilling the values of tolerance, mutual respect, and inclusive attitudes in students in a diverse society. However, the implementation and concrete impact of multicultural education at the secondary school level, especially in the local context of Indonesia, are still rarely researched in depth. This study aims to examine the implementation of multicultural education at SMP Negeri 1 Kotapinang and analyze its impact on grade IX students' character-building and social attitudes. The approach used is qualitative with an analytical descriptive design. Data were collected through participatory observation, semi-structured interviews, documentation, and field notes. Informants comprised two principals, six teachers, and ten students purposively selected based on active involvement in the multicultural education program. Data validity was maintained through source and method triangulation. Analysis was conducted using the Miles and Huberman interactive model with inductive coding techniques to identify the main themes related to multicultural education's implementation, impact, and challenges. The research found three primary strategies in the implementation of multicultural education: (1) integration of diversity values in the learning process and student group dynamics; (2) interfaith religious classes that encourage dialogue and mutual understanding; and (3) use of innovative media such as Bhineka Chatbot as a means of learning diversity. These strategies shape an inclusive learning environment and increase students' social awareness. Multicultural education at SMP Negeri 1 Kotapinang has proven effective in shaping students' humanist character and strengthening their social attitudes. The findings provide a practical contribution to developing diversity-based character education policies at the secondary school level.